Adapting an Undergraduate Multiliteracies German Curriculum for Online Instruction During the COVID-19 Pandemic - Cunningham, D. Joseph (Íkala, Revista de Lenguaje y Cultura, 2021)
This article reports on the adaptation of an undergraduate German curriculum for a distance language education (dle) context. Understanding that dle has evolved over the course of decades, the article reviews literature describing pedagogical and technological developments that are fundamental to understanding current practices in dle. Against this backdrop, a detailed methodology is presented that explains the pedagogical practices that were adopted and adapted following the pandemic-induced shift from classroom-based teaching to dle. Special attention is devoted to the role of synchronous instruction, as well as asynchronous tools that support multiliteracies instruction. The article concludes by considering those curricular innovations that are likely to have a long-lasting impact on the delivery of instruction following a return to classroom-based teaching.